2009
DOI: 10.1146/annurev-nutr-080508-141134
|View full text |Cite
|
Sign up to set email alerts
|

Is There Glucose Production Outside of the Liver and Kidney?

Abstract: This review analyzes the evidence presented to support the role of organs other than the liver and kidney to release substantial amounts of glucose into the mammalian blood circulation. The evidence includes (a) the identification of gluconeogenic enzyme activities in various organs, especially the small intestine, (b) levels of mRNA for the same enzymes, and (c) measurements of gluconeogenic flux in the small intestine. The latter would be the definite proof of extrahepatic, extrarenal glucose production. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 73 publications
1
23
1
1
Order By: Relevance
“…Gluconeogenic activity is not normally presented in cells that are not originated from liver, kidney, intestine or muscle (53). The glycogenic feature of brain metastatic cells enables another pro-survival ability to these cells, glucose storage, which helps cancer cells to resist external metabolic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Gluconeogenic activity is not normally presented in cells that are not originated from liver, kidney, intestine or muscle (53). The glycogenic feature of brain metastatic cells enables another pro-survival ability to these cells, glucose storage, which helps cancer cells to resist external metabolic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting intestinal glucose release, detected by a hepatoportal sensor, activates hypothalamic nuclei involved in the regulation of food intake. Whereas some authors claim for no credible evidence to support the concept that glucose can be produced by intestine (43), it has been recently demonstrated that protein-induced satiety was abolished in the absence of intestinal gluconeogenesis in mice with intestine-specific deletion of the glucose-6-phosphatase (42). This points to the importance of protein absorption mediated by PEPT1 in the control of body energy homeostasis and is also in line with the improved glucose homeostasis reported in obese diabetic patients fed on a protein-enriched diet (53).…”
Section: Discussionmentioning
confidence: 99%
“…Although the small intestine in adult mammals is thought to have a low capacity for gluconeogenic activity (41), recent studies (reviewed in Ref. 35) suggest that intestinal gluconeogenesis may contribute up to 25% of total endogenous glucose production during fasting, thereby, via the periportal neural system, modulating hunger sensations and whole body glucose homeostasis, especially between meals.…”
Section: R505 Fructose Regulates Fructolytic and Gluconeogenic Genesmentioning
confidence: 99%